2021
DOI: 10.3390/ijfs9010009
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Perceived Risks in the Relationship between Financial Knowledge and the Intention to Invest in the Saudi Arabian Stock Market

Abstract: This research study aims to investigate the moderating role of perceived risks in the relationship between financial knowledge (represented by objective knowledge and subjective knowledge) and the intention to invest in the Saudi Arabian Stock Market. The researcher collected data from four hundred Saudi Arabian participants who were interested in investing in the Saudi Arabian Stock Market. The researcher used structural equation modeling (SEM) through the Smart PLS 3.3.2 software to analyze the data. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 30 publications
2
16
0
4
Order By: Relevance
“…Trang and Tho’s ( 2017 ) found that perceived risk positively affects their investment decisions bringing satisfaction. Shehata et al ( 2021 ) supported that perceived risk calculation boosts the investor’s confidence while stock exchange trading, thus increasing investor intention. Maziriri et al ( 2019 ) found that all the elements of perceived risk affect the investor's intention while trading on online platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Trang and Tho’s ( 2017 ) found that perceived risk positively affects their investment decisions bringing satisfaction. Shehata et al ( 2021 ) supported that perceived risk calculation boosts the investor’s confidence while stock exchange trading, thus increasing investor intention. Maziriri et al ( 2019 ) found that all the elements of perceived risk affect the investor's intention while trading on online platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, investment awareness with investment rules, regulations, policies and knowledge influences intention to invest [44]. Shehata et al [45] concluded in a recent study that an investor's intent to invest in the Saudi Arabian Stock Exchange positively correlates with his or her awareness of investing risks. Despite this, Octarina et al [46] argued that investment awareness has no significant impact on the student's intention to invest; Ammer and Aldhyani, [9] confirmed that investment awareness positively influences students' intentions toward investment.…”
Section: Investment Awareness and Financial Risky Investment Intentionsmentioning
confidence: 99%
“…The primary relationship means that financial market decisions reflect trends in oil prices. For instance, the listing of Saudi Aramco, the primarily state-owned oil exploration company by Saudi Arabia, on the Saudi Arabian Stock Market was a strategic move to invite external investors (Shehata et al, 2021). The invitation of external investors was motivated by a need for the government to stabilize Saudi Arabia's financial markets further.…”
Section: Literature Reviewmentioning
confidence: 99%